Utilization of Remote Sensing Techniques for Monitoring and Evaluation of Solo Watershed Management - Gunawan, Totok (Forum Geografi, 2003)
This research is an application of remote sensing technology for monitoring and evaluation of watershed management, which was conducted is Solo Watershed, Central and East Java. The research objectives were 1) to investigate the capability of photomorphic analysis of Landsat Thematic Mapper (TM) and Enhanced Themmatic Mapper (ETM +) imagery as the basic for analyzes of landforms, landuse, and morphometry of the land surface; 2) to calculate the overland flow â peak discharge and erosion â sediment yield as indicators of land degradation of the area; 3) to use the indicators as set of instrument for monitoring and evaluation of watershed management. In this study, visual interpretation by means of on-screen digilization of the digital imagery was carried out in order to identify and to delineate land parameters using photomorphic approach. Based on the photomorphic analysis, several image â based parameters such as relief topography, physical soil characteristic, litho â stratigraphy, and vegetation cover were integrated with other themati maps in a geographic information system (GIS) environment. Estimation of overland flow (C) based on Cook methods (1942) and calculation of peak disccharge (Qmax) based on rational method (Qmax = C. I. A) were applied. Meanwhile, estimation of surface erosion was carried out using Universal Soil Loss Equation (USLE, A = R. K. L. S. CP). The sediment yield (Sy) was estimated using seddiment delivery ratio ( SDR) based on the following formula: Sy = [A + (25% x A)] x SDR. Both pairs of C â Qmax and A â Sy, were utilized as the basis for monitoring and evaluation of the watershed. The combination of C â Qmax and A â Sy were also used as the basis for selection of stream gauge setting / AWLR within particular sub â catchment. It was found that the photomorphic analysis is only color/tone, slope aspects, pattern, and texture, unit boundaries between volcanic â origin landscape (Wilis volcanic complex) and folded â hills landforms (Kendeng ridges) can be delineated. Within the volcanic features, coarse â textured units indicating pyroclastic materials with high drainage density (western part of Lawu volcano). In terms of calculated overland flow and peak discharge of 100 sub â catchment within the Solo Watershed, it was found that there are four sub â catchment with relatively high values (> 0.60 and > 1200 m3s1 for overland flow and peak discharge repectively), namely Samin (Karanganyar), Keduang (Wonogiri), Dengkeng (Klaten), and Sungkur (Ponorogo). Five sub-catchment might be categorized as having moderate peak discharge (Qmax ranges from 1000 â 1200 m3s1), namely Ketonggo (Ngawi), Keyang (Ponorogo), Gandong â Semawur (Magetan), Pepe (Boyolali), and Soko (Bojonegoro), while the remaining 91 sub-catchments are categorized as having low peak discharge. Based on the calculation of erosion and sediment yield, there was no sub-catchment with moderate category (60 â 180 ton ha1yr1), i.e. Samin (Karanganyar), Gonggong (Magetan), Ngisip and Kedung Cilik (Tuban), and Pepe (Boyolali). The other 95 sub-catchment might be categorized as gentle to good. In terms of values representing overland flow â flood and erosion â sediment yield, there are several sub-catchments require first priority in monitoring and evaluation, and are recommended as suitable sites for stream gauge setting, i.e. Samin (Karanganyar), Gonggong (Magetan), Ngisip and Kedung Cilik (Tuban).